2019
DOI: 10.9779/pauefd.446654
|View full text |Cite
|
Sign up to set email alerts
|

Dijital Oyun Popüler mi? Ebeveynlerin Çocukları İçin Oyun Tercihlerinin İncelenmesi

Abstract: Digital play has entered into houses and the lives of children and brought many debates with it. In spite of debates the number of research is very limited. For this reason, the purpose of this research is to examine parents' play preferences for their children by focusing on the digital play. 351 parents having a child attending preschools participated in this research. The data were collected through the Parental Play Preference Scale developed by the paired comparison method. Two-way ANOVA and MANOVA were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 25 publications
0
14
0
17
Order By: Relevance
“…Digital play includes playing digital games and applications, watching, and making videos, and taking pictures. This new form of play has become an increasingly popular and cultural context for young children (Edwards, 2018 ; Işıkoğlu Erdoğan, 2019 ; Heider & Jalongo, 2015 ). Currently, researchers argue that digital play is just a play for children, and their traditional play activities and engagement with digital play become interwoven (Bird & Edwards, 2014 ; Edwards, 2018 ; Marsh, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital play includes playing digital games and applications, watching, and making videos, and taking pictures. This new form of play has become an increasingly popular and cultural context for young children (Edwards, 2018 ; Işıkoğlu Erdoğan, 2019 ; Heider & Jalongo, 2015 ). Currently, researchers argue that digital play is just a play for children, and their traditional play activities and engagement with digital play become interwoven (Bird & Edwards, 2014 ; Edwards, 2018 ; Marsh, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with these recommendations, more than two hours of daily use of digital devices was considered as overuse in this study. Several studies have also shown that young children are often exposed to the screen for more than the recommended time (Işıkoğlu Erdoğan, 2019 ; Lauricella, Wartella, & Rideout, 2015 ; Montag & Walla, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire does not borrow questions from another instrument and was developed in accordance with steps for developing items in measurement and evaluation tools [78]. A literature review was conducted in order to establish validity by deriving from recent studies in the same field [5,24,25,[79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. In addition, informal meetings were carried out with preschool teachers who have preschool children of their own, in order to consult their evaluations regarding digital parenting.…”
Section: Digital Parenting Questionnairementioning
confidence: 99%
“…Güncel bir araştırmada 3-6 yaş çocukların %64.3'ünün cep telefonuyla oyun oynadıkları, %87.4'ünün cep telefonuyla çizgi film izledikleri, %34.6'sının ebeveynlerinin varsa tablet/bilgisayarı kullanmak istedikleri saptanmıştır (Kadan ve Aral, 2018). Benzeri bir araştırmada 4-6 yaş çocukların ortalama 182 dakika ekran karşısında geçirdikleri saptanmıştır (Işıkoğlu Erdoğan, 2019). Araştırmalar ebeveynlerin dijital araçları çocuklarına satın aldıkları ve kullanmalarına izin verdikleri halde dijital oyunlarla ilgili endişeler taşıdıkları saptanmıştır (Günüç ve Atlı, 2018;Işıkoğlu Erdoğan, 2019;Nevski ve Siibak, 2016;Terras ve Ramsay, 2016).…”
Section: Introductionunclassified
“…Benzeri bir araştırmada 4-6 yaş çocukların ortalama 182 dakika ekran karşısında geçirdikleri saptanmıştır (Işıkoğlu Erdoğan, 2019). Araştırmalar ebeveynlerin dijital araçları çocuklarına satın aldıkları ve kullanmalarına izin verdikleri halde dijital oyunlarla ilgili endişeler taşıdıkları saptanmıştır (Günüç ve Atlı, 2018;Işıkoğlu Erdoğan, 2019;Nevski ve Siibak, 2016;Terras ve Ramsay, 2016). Benzer şekilde, ailelerin dijital oyunların eğitim amaçlı kullanılabileceğine dair görüşleri düşük düzeyde bulunmuştur (Aral ve Doğan Keskin, 2018).…”
Section: Introductionunclassified